2023
DOI: 10.3390/jcm12062169
|View full text |Cite
|
Sign up to set email alerts
|

Examining Clinical Opinion and Experience Regarding Utilization of Plain Radiography of the Spine: Evidence from Surveying the Chiropractic Profession

Abstract: Plain Radiography of the spine (PROTS) is utilized in many forms of healthcare including the chiropractic profession; however, the literature reflects conflicting opinions regarding utilization and value. Despite being an essential part of Evidence-Based Practice (EBP), few studies assess Doctors of Chiropractic (DCs) clinical opinions and experience regarding the utilization of (PROTS) in practice. In this study, DCs were surveyed regarding utilization of PROTS in practice. The survey was administered to an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 110 publications
(108 reference statements)
0
0
0
Order By: Relevance
“…At the time of the writing of this Editorial, there were 15 unique manuscripts accepted for publication in the Special Issue: Spine Rehabilitation in 2022 and Beyond. These manuscripts include the following categories of articles: a cross-sectional survey comparing two distinct quality of life questionnaires in adults with scoliosis [46]; a retrospective consecutive cohort investigation examining the relationship of vertebral y-axis rotation of the lumbar spine in functional scoliosis with leg length inequality to sacral shelf lateral tilt angles [47]; a profession wide survey of the chiropractic profession regarding spine radiography utilization examining clinical opinions and experience [48]; a novel clinical manual method comparing manual palpation and motion vs. diagnostic imaging to determine pathological rotational instability movement of the upper cervical spine [49]; four case-control investigations seeking to identify any correlations between spine and posture displacements and patient pain, disability, neurophysiology, and sensory-motor control variables [50][51][52][53]; one case series looking at the relationship between non-surgical sagittal plane cervical spine correction and the improvement in upper cervical spine rotational instability [54]; five randomized trials examining the relationship between correction/reduction of cervical and thoracic posture deformities and spine displacements and improvements of a variety of clinical outcome measures including pain, disability, neurophysiology, range of motion, and sensory-motor control measures [55][56][57][58][59]; and, lastly, one systematic literature review that sought to understand the differences in low back pain and disability characteristics in adults with and without scoliotic spine deformities [60].…”
Section: Special Issue Main Accepted Articlesmentioning
confidence: 99%
See 2 more Smart Citations
“…At the time of the writing of this Editorial, there were 15 unique manuscripts accepted for publication in the Special Issue: Spine Rehabilitation in 2022 and Beyond. These manuscripts include the following categories of articles: a cross-sectional survey comparing two distinct quality of life questionnaires in adults with scoliosis [46]; a retrospective consecutive cohort investigation examining the relationship of vertebral y-axis rotation of the lumbar spine in functional scoliosis with leg length inequality to sacral shelf lateral tilt angles [47]; a profession wide survey of the chiropractic profession regarding spine radiography utilization examining clinical opinions and experience [48]; a novel clinical manual method comparing manual palpation and motion vs. diagnostic imaging to determine pathological rotational instability movement of the upper cervical spine [49]; four case-control investigations seeking to identify any correlations between spine and posture displacements and patient pain, disability, neurophysiology, and sensory-motor control variables [50][51][52][53]; one case series looking at the relationship between non-surgical sagittal plane cervical spine correction and the improvement in upper cervical spine rotational instability [54]; five randomized trials examining the relationship between correction/reduction of cervical and thoracic posture deformities and spine displacements and improvements of a variety of clinical outcome measures including pain, disability, neurophysiology, range of motion, and sensory-motor control measures [55][56][57][58][59]; and, lastly, one systematic literature review that sought to understand the differences in low back pain and disability characteristics in adults with and without scoliotic spine deformities [60].…”
Section: Special Issue Main Accepted Articlesmentioning
confidence: 99%
“…Importantly, each one of these 15 accepted manuscripts offers unique and succinct relevant data that provide further evidence that the 'bio' (biology and biomechanics) component of the 'bio-psycho-social' model of spine care is extremely important to understanding patient pain, disability, and dysfunction and to providing enhanced treatment procedures that improve the outcomes of patient care [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. As such, this Special Issue on spine rehabilitation provides useful, cutting-edge, relevant information that should prove to be useful to improve patient care and outcomes in populations suffering from a wide variety of spine related disorders.…”
Section: Special Issue Main Accepted Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…While some chiropractors primarily use radiographs to rule out serious pathology and trauma, which is in line with CPGs [ 9 , 17 ], others consider such recommendations to be too restrictive. Some chiropractors suggest that radiographs are additionally necessary in the assessment of structural misalignment, to determine/guide appropriate treatment, and to identify clinically unsuspected contraindications to management [ 18 , 19 ]. For example, a survey of United States (US) chiropractors reported that 87% of chiropractors thought obtaining radiographs for biomechanical analysis has significant value, and 72% of chiropractors reported using radiographs to determine where and how to perform spinal manipulation (SM) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some chiropractors suggest that radiographs are additionally necessary in the assessment of structural misalignment, to determine/guide appropriate treatment, and to identify clinically unsuspected contraindications to management [ 18 , 19 ]. For example, a survey of United States (US) chiropractors reported that 87% of chiropractors thought obtaining radiographs for biomechanical analysis has significant value, and 72% of chiropractors reported using radiographs to determine where and how to perform spinal manipulation (SM) [ 19 ]. Similarly, in Australia, approximately one-third of chiropractors mentioned that they would refer for radiographs to perform biomechanical analyses, and approximately two-thirds stated that they would use radiographs to assess patients for less serious conditions (e.g., spinal curve changes, spondylolisthesis, or degeneration) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%